Digital Governance Challenges: The Digital Divide and Government Infrastructure Limitations in Sri Lanka - Perera, Nimal; Wijesinghe, Sachini; Jayawardena, Tharindu (Asian Digital Governance Problems, 2026)
Purpose: This study aims to examine the challenges of digital governance in Sri Lanka, with a particular focus on the digital divide and government infrastructure limitations. It seeks to understand how structural, institutional, and socio-cultural factors shape the effectiveness and inclusivity of digital governance initiatives in a developing country context. Subjects and Methods: The research adopts a qualitative design, drawing on data from 25 semi-structured interviews with government officials, IT practitioners, policy advisors, and citizens from urban, rural, and estate sectors. Participants were selected using purposive sampling to capture diverse perspectives and experiences related to digital governance. Data were analyzed using thematic analysis through an iterative coding process to identify recurring patterns and key themes. Results: The findings reveal six interrelated challenges: regional inequality in digital infrastructure, digital literacy gaps, institutional fragmentation, reliance on hybrid online–offline practices, trust deficits, and policy–practice gaps. Uneven infrastructure and limited digital skills restrict meaningful citizen participation, particularly in rural and estate areas. Institutional capacity constraints, lack of system integration, and limited trust in digital platforms further reduce the transformative potential of digital governance, resulting in partial and uneven implementation across regions. Conclusions: The study concludes that digital governance in Sri Lanka is constrained by multidimensional structural and institutional barriers. Sustainable and inclusive digital transformation requires integrated strategies that address infrastructure equity, digital literacy, institutional coordination, and trust-building, rather than a sole emphasis on technological adoption.